Selection of Digestive Tract Reconstruction After Partial Gastric Sparing Surgery in Patients With Adenocarcinoma of the Esophagogastric Junction of cT2-T3 Stage - Zhang, Junli; Zhang, Xijie; Li, Sen; Liu, Chenyu; Cao, Yanghui; Ma, Pengfei; Li, Zhenyu; Li, Zhi; Zhao, Yuzhou (Frontiers in Surgery, 2022)
To investigate the appropriate reconstruction method of the digestive tract after partial gastric sparing surgery for adenocarcinoma of the esophagogastric junction of stage cT2-T3 . Methods A retrospective analysis of the clinical data of patients with adenocarcinoma of the esophagogastric junction from January 2015 to January 2019 in the General Surgery Department of Zhengzhou University Affiliated Tumor Hospital was performed. Patients with intraoperative double tract anastomosis composed the double tract reconstruction (DTR) group, and patients with intraoperative oesophagogastrostomy with a narrow gastric conduit group composed the oesophagogastrostomy by a narrow gastric conduit (ENGC) group. We analysed and compared the short-term postoperative complications and long-term postoperative nutritional status of the two groups of patients. Result The gastric resection volume of the DTR group was much larger than that of the ENGC group, and there was a significant difference between the two (p=0.000). The length of the lower resection margin of the DTR group was also significantly greater than that of the ENGC group (p=0.000). In terms of surgical approach, the proportion of the DTR group with the abdominal approach was significantly higher than that of the ENGC group, and the difference between the two was statistically significant (p=0.007). The postoperative exhaust time in the ENGC group was significantly shorter than that in the DTR group (p=0.013). In terms of anastomotic stenosis, the incidence in the ENGC group was higher than in the DTR group, and the difference was statistically significant (p=0.001). In terms of poor swallowing, the ENGC group was always higher than the DTR group, and the difference between the two groups was statistically significant (p<0.05). At 12 months after surgery, the body weight of the patients in ENGC group was significantly higher than that in the DTR group, and the difference between the two groups was statistically significant (p=0.039). Conclusions For patients with cT2-T3 stage oesophagogastric junction adenocarcinoma with tumours less than 4 cm in diameter, ENGC anastomosis is recommended for patients with a high tumour upper boundary, with obesity, short mesentery, or disordered vascular arch, and for routine patients, DTR anastomosis is recommended.